Plan de marketing utilizando la estrategia de comunicación digital para la empresa Malca del cantón Catamayo - Vicuña Gutiérrez, Julio César (2023)
This research paper called "A marketing plan based on a digital communication strategy for the company Malca from the Catamayo canton" sought to enhance the sugar company’s online communication, thus improving its visibility, brand image, customer relationship and sales. T wa set as a general objective to develop a marketing plan using the digital communication strategy. The research was structured into three specific objectives. First, a market analysis was performed, using an exploratory-descriptive approach. Data was collected from 9 suppliers and industries in different provinces of Ecuador that trade Malca products. The main tools were an interview with the manager and head of marketing, along with surveys applied using Google Forms and statistical analysis with IBM SPSS. The second objective focused on a diagnosis of the current situation of the company, using the 7 P framework of marketing. Also, internal aspects were evaluated using an EFI matrix, which showed that Malca had more strengths than weaknesses. In addition, external factors were analysed through a PESTEC analysis, which indicated that the company was responding favourably to opportunities and threats in the environment. The third objective was to design concrete strategies. It was proposed micro and macro strategies, such as the creation of social networks, the development of a new packaging, the creation of a slogan, the improvement of the corporate image and the implementation of a chat-bot on the website. These strategies would require a total investment of $13,707.50. Based on the results obtained, conclusions and recommendations were derived to meet the objectives set.